2018
DOI: 10.1016/j.epsl.2018.05.043
|View full text |Cite
|
Sign up to set email alerts
|

A Neogene history of mantle convective support beneath Borneo

Abstract: Most, but not all, geodynamic models predict 1-2 km of mantle convective draw-down of the Earth's surface in a region centered on Borneo within southeast Asia. Nevertheless, there is geomorphic, geologic and geophysical evidence which suggests that convective uplift might have played some role in sculpting Bornean physiography. For example, a long wavelength free-air gravity anomaly of +60 mGal centered on Borneo coincides with the distribution of Neogene basaltic magmatism and with the locus of sub-plate slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 64 publications
(130 reference statements)
2
33
1
Order By: Relevance
“…For the inverse model, a value of λ s ≈ 1 produces a combination of suitable model roughness (a small “model norm”) and low rms misfit for Calabria (Figure 8a), which is similar to the optimal value used in many previous studies (e.g., Conway‐Jones et al., 2019; Roberts et al., 2018; Rudge et al., 2015). Therefore, our uplift analysis will initially consider inverse models with λ s = 1.…”
Section: Resultssupporting
confidence: 74%
“…For the inverse model, a value of λ s ≈ 1 produces a combination of suitable model roughness (a small “model norm”) and low rms misfit for Calabria (Figure 8a), which is similar to the optimal value used in many previous studies (e.g., Conway‐Jones et al., 2019; Roberts et al., 2018; Rudge et al., 2015). Therefore, our uplift analysis will initially consider inverse models with λ s = 1.…”
Section: Resultssupporting
confidence: 74%
“…This magmatism, or the increased heatflow associated with it, was most probably responsible for causing crustal melting. Roberts et al (2018) suggested that the mantle beneath Borneo is hotter than ambient mantle but a hotspot origin can be discounted for the West Sarawak and Kalimantan Sintang magmatism.…”
Section: Cause Of Magmatismmentioning
confidence: 99%
“…The lithosphere of Borneo is thinner than adjacent portions of the Sunda Shelf (Roberts et al, 2018) and the extensive Kuching depocentre implies that a broad swathe of crust between the Lupar Line and the Schwaner Mountains experienced substantial crustal thinning from the Cretaceous until the mid-Cenozoic (Eocene-Oligocene) (Fig. 11a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Topography is the result of complex interactions between the solid Earth and surface processes that operate on multiple spatial and temporal scales (e.g., Anderson & Anderson, 2010;Roberts et al, 2019). Consequently, surface uplift and subsidence histories have been combined with magmatic and tomographic information to estimate temperatures, wavelengths, and timescales of mantle convection (e.g., Gurnis et al, 2000;Lodhia et al, 2018;Roberts et al, 2018;Salles et al, 2017;van Wijk et al, 2010). The results of these studies imply that mantle processes play a significant role in driving the erosional history of a landscape.…”
Section: Introductionmentioning
confidence: 99%